EFEKTIVITAS DAN EFISIENSI TEKNIK ISOLASI DAN PURIFIKASI DNA PADA JAMBU METE - ., Syafaruddin; Randriani, Enny; Santoso, Tri Joko (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
Effectivity and efficiency of DNA isolation and purification technique on cashew plant. Cashew well known as a potential industrial plant to be expanded due to of kernel price and cashew can also be used as conservation plant. As a potential plant, so needed informationmore detail including the molecular information. There are many techniques to conduct DNA isolation depend on kind of plants or plant tissue thatwill be used. The experiment had been conducted at Molecular Biology Laboratory of Indonesian Center for Agricultural Biotec hnology and GeneticResources Research and Development (BB BIOGEN), Bogor on May-July 2011. Young leaf of cashew used as genetic materials which is took fromexperimental station Cikampek, Indonesian Spice and Industrial Crops Research Institute (BALITTRI). While some chemicals were used as the other material. The activities following step: DNA extraction and purification, measurement of DNA concentration and amplification of DNA. Deletion ofresistor enzyme-polysacharide, especially for perennial plant. DNA isolation can be done by breaking down of cell wall, cell membrane and nuclearmembrane. The aim of this experiment was to find the effectivity and efficiency technique of DNA isolation and purification so can be reducing costand time consuming while working in the laboratory. The results shows that conscientiousness of DNA isolation and purification denotes an importantstep to obtain clean and contaminant free of DNA, so banding pattern will be clear. In this technique did not used polypinilpolypirolidone (PVPP)and mercapto-ethanol such as antioxidant, liquid nitrogen, neither over night storage of leaf extraction before used for purification which is often used for perennial plant. In addional, the results shows that band pattern of DNA was very thick and clear, therefore, this techni que can be used for DNA isolation on cashew.